Peran Mahasiswa KKN dalam Meningkatkan Kesadaran Hidup Sehat melalui Pemanfaatan Botol Bekas sebagai Wadah Menabung di Desa Mesjid Lama - Hidayah, Chintia Gustira; Syahputri, Hindri; Amanda, Gita; Tryadi, Dicka; Analus, Papi; Malango, Tinur Baya (Universitas Mataram, 2025)
Real Work Lecture (KKN) activities are a form of student service to the community through educational and useful programs. This study aims to describe the role of KKN students in increasing awareness of healthy living and fostering the habit of saving from an early age by using used bottles as piggy banks in the Old Mosque Village. The method used is qualitative descriptive through observation, interviews, and documentation. The results of the activity showed that the creative approach of KKN students was able to attract students' interest in saving as well as introducing wise plastic waste management. Plastic that is not managed properly has the potential to pollute the environment and trigger health problems, ranging from respiratory disorders, hormones, to cancer risk due to harmful substances and microplastics. Thus, this activity not only instills the value of discipline and responsibility, but also increases awareness of the dangers of plastic waste. The program received a positive response from the school and had a lasting impact.